Short-term influences of flow alteration on microbial community structure and putative metabolic functions in gravel bar hyporheic zones - Doloiras-Laraño, Arnelyn D.; Serrana, Joeselle M.; Takahashi, Shinji; Takemon, Yasuhiro; Watanabe, Kozo (Frontiers in Environmental Science, 2023)
Microbial communities in the hyporheic zone are important for self-purification as the riverbed is metabolically active and responsible for the retention, storage, and mineralisation of organic matter transported in the surface water. Studies exploring the response of the hyporheic microbial community to flow regime alterations remain scarce. Here, we characterised the microbial community structure over downwelling, upwelling and intermediate hyporheic zone areas within and among gravel bars at high and low discharge levels to determine flow-induced changes in a dam-regulated river using 16S rRNA gene sequencing. At low discharge, microbial composition varied across the different areas of gravel bars, reflecting heterogeneity in local abiotic conditions. However, high discharge lead to microbial community homogenisation across the three areas of the gravel bars. Microbial communities across adjacent gravel bars remained dissimilar regardless of discharge levels, likely reflecting differences in bar morphology. Our results can help better understand how anthropogenic changes in hydrologic conditions can affect microbial diversity and function in the hyporheic zone. This knowledge will help us to understand better how changes in hydrological conditions affect ecosystem functions and services in rivers affected by human impacts.